Hydrogen Sulfide Attenuated Sepsis-Induced Myocardial Dysfunction Through TLR4 Pathway and Endoplasmic Reticulum Stress - Chen, Yu-hong; Teng, Xu; Hu, Zhen-jie; Tian, Dan-yang; Jin, Sheng; Wu, Yu-ming (Frontiers in Physiology, 2021)
Aims: We examined the change in endogenous hydrogen sulfide (H2S) production and its role in sepsis-induced myocardial dysfunction (SIMD). Results: Significant elevations in plasma cardiac troponin I (cTnI), creatine kinase (CK), tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β) were noted in SIMD patients, whereas left ventricular ejection fraction (LVEF), left ventricular fractional shortening (LVFS), and plasma H2S were significantly decreased relative to those in the controls. Plasma H2S was linearly related to LVEF and LVFS. Subsequently, an SIMD model was developed in mice by injecting lipopolysaccharide (LPS), and NaHS, an H2S donor, was used to elucidate the pathophysiological role of H2S. The mice showed decreased ventricular function and increased levels of TNF-α, IL-1β, cTnI, and CK after LPS injections. Toll-like receptor (TLR) 4 protein and endoplasmic reticulum stress (ERS) proteins were overexpressed in the SIMD mice. All of the parameters above showed more noticeable variations in cystathionine γ-lyase knockout mice relative to those in wild type mice. The administration of NaHS could improve ventricular function and attenuate inflammation and ERS in the heart. Conclusions: Overall, these findings indicated that endogenous H2S deficiency contributed to SIMD and exogenous H2S ameliorated sepsis-induced myocardial dysfunction by suppressing inflammation and ERS via inhibition of the TLR4 pathway.